Benign Acute Childhood Myositis associated with Influenza Virus Infection: A Case Series in Zawia Teaching Hospital - Mufida Khetresh,; Nasreen Alarosi,; Kheria Almamori, (AlQalam Journal of Medical and Applied Sciences, 2024)
Benign acute myositis of childhood is a disorder of childhood, typically affecting boys. Symptoms include calf pain and difficulty walking after a prodromal viral upper respiratory illness. We report four cases of benign acute childhood myositis BACM in children diagnosed at Zawia Teaching Hospital had the typical clinical and laboratory characteristics of this clinical syndrome. Prompt diagnosis of this clinical disease essential to prevent unnecessary investigations and therapeutic interventions and to reassure the patient and parents of the excellent prognosis. The real time polymerase chain reaction test (RT-PCR) was used to detect influenza viruses from respiratory sample in all of them. Influenza B was determined in 3 patients (75%), and influenza A in 1 patient (25%). The Mean age was 7.25 years (4-11) and all of them were male and Urine analysis was not request for myoglobinuria. Influenza viruses, particularly H1N1 variants, can induce BACM and other types of muscular diseases. The Correct diagnosis by recognition of characteristic clinical, laboratory features of BACM and history of the preceding viral illness, as outlined in our case series provides cost effective and appropriate approach for diagnosis and prevent unnecessary treatment and diagnostic procedures. It is important to recognize BACM as self-limiting condition which could however be mistaken for a more aggressive disease. التهاب العضلات الحاد الحميد في مرحلة الطفولة هو اضطرابات عضلية وعادة تؤثر على الأولاد أكثر من البنات. تشمل الأعراض ألمًا في ربلة الساق وصعوبة في المشي بعد اعراض أمراض الجهاز التنفسي العلوي الفيروسية. تمت دراسة أربع حالات من مجموعة اطفال دخلوا الي المستشفى وتم تشخيصهم وفقا للخصائص السريرية والمخبرية لهذه المتلازمة السريرية. إن التشخيص الفوري لهذا المرض السريري ضروري لمنع الفحوصات والتدخلات العلاجية غير الضرورية وطمأنة المريض والوالدين على التشخيص الممتاز تم استخدام اختبار تفاعل البوليميرات المتسلسل للكشف عن فيروسات الأنفلونزا من عينة الجهاز التنفسي في كل حالة منهم, وتم تحديد فيروس الأنفلونزا B في 3 مرضى (75%)، وفيروس الأنفلونزا A في مريض واحد (25%). وكان متوسط ​​العمر 7.25 سنة (4-11) وجميعهم من ذكور يمكن لفيروسات الإنفلونزا، وخاصةً فيروسات H1N1 أن تحفز الإصابة بالتهاب العضلات وأنواع أخرى من الأمراض العضلية. من المهم التعرف على تحفز الإصابة بالتهاب العضلات كمرض يختفي من تلقاء نفسه دون علاج ومع ذلك، يجب عدم الخلط بينه وبين مرض أكثر عدوانية